The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jog.13078
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of placental elasticity in normal and pre‐eclamptic pregnant women by acoustic radiation force impulse elastosonography

Abstract: The stiffness of the placenta determined by the ARFI technique is significantly higher in pre-eclampsia patients. ARFI elastography of the placenta might be used as a non-invasive and easy method in the diagnosis and evaluation of pre-eclampsia as a supplement to the already existing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 20 publications
3
37
0
1
Order By: Relevance
“…There is limited data regarding ARFI scores changes during different gestational weeks. The studies involving ARFI examinations included the third trimester of gestation in the literature [13,19]. We did not evaluate the histopathologic findings of the placentas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is limited data regarding ARFI scores changes during different gestational weeks. The studies involving ARFI examinations included the third trimester of gestation in the literature [13,19]. We did not evaluate the histopathologic findings of the placentas.…”
Section: Discussionmentioning
confidence: 99%
“…There have been limited studies concerning ARFI investigating placental elasticity [17][18][19]. Sugitani et al [13] measured the placental elasticity by using ARFI in an ex vivo study and they found higher ARFI scores in intrauterine growth restricted and hypertensive pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this method is not only useful for liver stiffness measurement but also for determination of changes in stiffness of the spleen[48], testis[49], thyroid[50], breast[51], placenta[52], pancreas in chronic pancreatitis[53] and transplanted kidney[54]. The technique is based on an acoustic impulse and measurement of the speed of the shear wave induced by it; results are displayed in m/s.…”
Section: Sonoelastrographymentioning
confidence: 99%